Precision integration of uniform molecular-level carbon into porous silica framework for synergistic electrochemical activation in high-performance lithium–ion batteries - Oh, Seungbae; Dong, Xue; Woo, Chaeheon; Zhang, Xiaojie; Kim, Yeongjin; Choi, Kyung Hwan; Lee, Bom; Kim, Ji Hee; Kang, Jinsu; Bang, Hyeon Seok; Jeon, Jiho; Oh, Hyung Suk; et al. (EcoMat, 2024)
The development of advanced anode materials for lithium-ion batteries that can provide high specific capacity and stable cycle performance is of paramount importance. This study presents a novel approach for synthesizing molecular-level homogeneous carbon integration to porous SiO2 nanoparticles (SiO2@C NPs) tailored to enhance their electrochemical activities for lithium-ion battery anode. By varying the ratio of the precursors for sol–gel reaction of (phenyltrimethoxysilane (PTMS) and tetraethoxysilane (TEOS)), the carbon content and porosity within SiO2@C NPs is precisely controlled. With a 4:6 PTMS and TEOS ratio, the SiO2@C NPs exhibit a highly mesoporous structure with thin carbon and the partially reduced SiOx phases, which balances ion and charge transfer for electrochemical activation of SiO2@C NPs resulting remarkable capacity and cycle performance. This study offers a novel strategy for preparing affordable high capacity SiO2-based advanced anode materials with enhanced electrochemical performances. (Figure presented.).
Keywords: anode; Li–ion battery; porous materials; SiO2@carbon nanoparticles